(untitled) (Physical Culture and Sport: Scientific Perspective, 2022)
The article presents the features of the structure and content of the general physical fitness of qualified rugby players specializing in rugby-7. Currently, the growing competition in the domestic sports arena makes significant demands on the level of general and special physical fitness of both individual players and teams as a whole. Therefore, a high level of their physical fitness is fundamental for the effective competitive activity of athletes. The purpose of the article was to study the structure and content of the general physical fitness of rugby players of different fitness levels. In order to achieve the goal, a pedagogical observation of the level of development of the physical qualities of the players of the participating teams of the Ukrainian Rugby 7 Championship of the 2021 season was carried out. Fifteen generally accepted tests used in sports games served as data for determining the level of physical fitness of qualified rugby players. To conduct the experiment, we divided the teams participating in the 2021 Ukrainian Rugby 7 Championship into two groups according to their position in the tournament table. A comparative analysis of the level of general physical fitness of the players of the teams of the Super League of the 2021 season of the Ukrainian rugby-7 championship shows that according to most of its indicators (7 out of 10), the rugby players of the leading teams with high reliability (p ≤ 0.01) prevailed over the players of the teams that took fifth to eighth place in the tournament table. In general, the obtained data adequately reflect the level of sportsmanship of the players of the specified teams, in particular, according to the places occupied by the teams at the time of testing, and therefore indicate that the applied tests directly or indirectly reflect the degree of readiness of rugby players for competitive activities. The results of the study prove the high significance of physical conditions in the structure of readiness of rugby players for effective competitive activity.